The snow lion and the dragon : China, Tibet, and the Dalai Lama - Goldstein, Melvyn C. (University of California Press, 1999)
Tensions over the "Tibet Question"--The political status of Tibet-are escalating every day. The Dalai Lama has gained broad international sympathy in his appeals for autonomy from China, yet the Chinese government maintains a hard-line position against it. What is the history of the conflict? Can the two sides come to an acceptable compromise? In this thoughtful analysis, distinguished professor and longtime Tibet analyst Melvyn C. Goldstein presents a balanced and accessible view of the conflict and a proposal for the future. Tibet's political fortunes have undergone numerous vicissitudes since.